Evaluation of Slovenian Occupational Therapists’ Theoretical Knowledge and Stress Levels Connected With Providing Cardiopulmonary Resuscitation - Damjan Slabe PhD; Alenka Oven PhD (Inquiry: The Journal of Health Care Organization, Provision, and Financing, 2020)
This was the first study that evaluated cardiopulmonary resuscitation (CPR) knowledge in a sample of occupational therapists and investigated whether the knowledge of CPR parameters affected their perceived stress levels related to providing CPR. A questionnaire, consisting of 4 clusters of questions, was pretested and used in an online survey of Slovenian occupational therapists. The survey was sent to all electronic addresses obtained from the Association of Occupational Therapists of Slovenia and the Faculty of Health Sciences at the University of Ljubljana. It was completed by 201 occupational therapists, which represented about 40% of all Slovenian occupational therapists. Data were analyzed using independent-samples t -test, 1-way ANOVA, and Pearson’s correlation coefficient. On average, the participants scored 5.44 points (SD = 2.96) on the CPR knowledge test that had a maximum of 9 points. A weak negative correlation existed between the perceived level of stress and scores on the knowledge test ( r  = −0.151; P  = .05). Scores on the knowledge test were also negatively correlated with age ( r  = −0.409; P  < .001) and work experience ( r  = −0.388; P  < .001) and positively correlated with self-evaluation of knowledge of CPR ( r  = 0.366; P  < .001). The majority of the participants (92.3%) felt that they needed to update their CPR knowledge. There was no statistically significant difference in the CPR knowledge between occupational therapists working in different clinical areas ( P  = .85). Our sample of occupational therapists was not optimally prepared to apply CPR. Older and more experienced therapists demonstrated less theoretical knowledge and were particularly vulnerable to stress. To improve knowledge and confidence, regular CPR training is recommended for this group of health professionals.